CHARACTERIZATION OF PROPERTIES OF PVDF/POLY(DIMETHYLSILOXANE) COMPOSITES SEPARATOR WITH BLENDING MEMBRANE METHOD - Devi Eka Septiyani Arifin (Journal of Natural Sciences and Mathematics Research, 2017)
The aims of this research to make poly(vinylidene fluoride) (PVDF) and poly(dimetilsiloksan) (PDMS) composites separator with blending membrane method. Synthesized of  PVDF/PDMS composites separator used various ratio were 10/0, 9/1, 8/2, and 7/3. The purpose of increasing concentration of PDMS/PVDF to improve the performance of the composites separator which includes a dimensions of porosity, a pore density, and a electrical conductivity. Based on crystallographic analysis using XRD, the increasing concentration number of PDMS to make compositess was influence decreasing of crystallinity until 29.26% in a ratio 7/3.The analysing of FTIR have sound the wavenumber of each phase can distinguish, which this material includes in the criteria of the composites. The result using XRD and FTIR to material PVDF/PDMS composites in all of the ratio constituens have shown the identification of the structure α-phase of PVDF. The increase of concentration number PDMS influenced decreasing of pore dimension and increasing of pore density with the small of pore dimension 1.71 µm and pore density 4.07x1011 count/m2 inthe ratio 7/3. In a ratio 7/3, the value of the electrical conductivity was 3.45x10-4S/cm and the resistance increased up to 80%.